2021
DOI: 10.3389/fpsyt.2021.655178
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Genetic Polymorphisms and Neuroimmune Markers With Some Parameters of Frontal Lobe Dysfunction in Schizophrenia

Abstract: We investigated the associations of DRD3 rs6280, HTR1A rs6295, BDNF rs6265, SCL6A4 rs16965628, and 5HT2A rs7322347 with schizophrenia in a case–control study, and associations of these genetic variants with several clinical features. We also investigated markers of inflammatory response (C-reactive protein, IL-2, IL-6, IL-10), the activity of leukocytic elastase (LE) and α1-proteinase inhibitor (a1-PI), antibodies to S100B and myelin basic protein (MBP) in schizophrenia. Clinical symptoms were assessed on thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Nonetheless, those authors explain that these results should be interpreted with caution because these are first-time studies, and the sample size is small [14]. The involvement of the immune system in the pathophysiology of schizophrenia is supported by the following findings: (a) an imbalance between pro-and anti-inflammatory cytokines and an effect of antipsychotic medication on their levels [15][16][17][18]; (b) activation of microglia, as confirmed by animal studies, postmortem brain studies, and positron emission tomography [19][20][21]; (c) higher prevalence of autoantibodies [22,23]; (d) activation of inflammation-related genes in the brain [24,25]; and (e) increased expression of proinflammatory genes in circulating monocytes [26]. Peripheral cytokines can cross the blood-brain barrier in patients with schizophrenia after damage but also bind to specific transporters, penetrate via afferent vagal fibers, and get access through circumventricular organs [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, those authors explain that these results should be interpreted with caution because these are first-time studies, and the sample size is small [14]. The involvement of the immune system in the pathophysiology of schizophrenia is supported by the following findings: (a) an imbalance between pro-and anti-inflammatory cytokines and an effect of antipsychotic medication on their levels [15][16][17][18]; (b) activation of microglia, as confirmed by animal studies, postmortem brain studies, and positron emission tomography [19][20][21]; (c) higher prevalence of autoantibodies [22,23]; (d) activation of inflammation-related genes in the brain [24,25]; and (e) increased expression of proinflammatory genes in circulating monocytes [26]. Peripheral cytokines can cross the blood-brain barrier in patients with schizophrenia after damage but also bind to specific transporters, penetrate via afferent vagal fibers, and get access through circumventricular organs [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Certain BDNF isoforms at low levels were consistently found to correlate with cognitive impairment in individuals with schizophrenia compared to controls ( 56 ). In line with these findings, Morozova ( 40 ) found that patients with genotype T/T (Met66Met polymorphism) demonstrated higher scores on PANSS, reflecting more severe symptoms, regardless of age. None of the other studies found a significant association between positive and negative PANSS scores and the Val66Met polymorphism, most focusing on the risk for schizophrenia or association with cognitive functions.…”
Section: Discussionmentioning
confidence: 72%
“…Looking at the association between the BDNF rs6265 and the TNF-α rs1799964 polymorphism in patients with schizophrenia, Zhang ( 28 ) found that the interaction of these two genes contributes to cognitive dysfunction, possibly by decreasing the expression of BDNF in the hippocampus. Only one study – Morozova ( 40 ) assessed immunological parameters along with their primary assessments, finding no association between genotype and immune status of patients, contrary to recent literature suggesting the contrary ( 3 ). Patients with schizophrenia have been found in numerous studies to present with upregulated genes for inflammatory cytokines and downregulated BDNF gene transcription ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In schizophrenia, a wide range of antinuclear antibodies, antineuronal antibodies [ 19 ], and antibodies to myelin are found [ 20 ]. Research by Kliushnik, T. et al indicated that antibodies to MBP may be related to the diagnosis of schizophrenia [ 21 , 22 ], and associated with the severity of clinical symptoms [ 23 ]. The different dynamics of immune markers, including autoantibodies to MBP, correspond to different features of clinical remission after first-episode psychosis in young patients [ 24 ].…”
Section: Introductionmentioning
confidence: 99%